CHARACTERISTICS OF TOURISM ACTIVITY IN AREAS OF HIGH NATURE VALUE - Romuald Ziółkowski (Acta Scientiarum Polonorum. Oeconomia, 2010)
The article examines selected aspects of tourist activity in areas of high nature value, presenting results of survey conducted among tourists. Research area was located in Podlaskie Province and included three units of nature – Knyszyńska Forest (an area with the largest landscape park in Poland), Biebrza Valley (the largest national park) and Narew Valley (as it is also located within the national park, with the smallest annual number of tourists in comparison to other national parks in Poland). The analysis allows to define preferred types of tourist activity, length of tourist stay, used transport means or motivations of visiting nature areas.